FINDING ADJECTIVES IN QURAN SURAH AL- KAHF - yusni sinaga (JURNAL LINER (Language Intelligence and Educational Research), 2022)
Looking at the limited time for people, especially for students and looking at so many subjects that must be studied by a student, it seems that students do not have time to study their religious. Where as in the curriculum of each subject is based on a character- based curriculum, means after following all subjects matter students are expected can keep good relations with their Creator and good relations to all creatures around them. Meanwhile, references to the teachings of the good character it self are only found in the students’ religious scriptures. Religious. The subjects matter presented at every level of elemntary school Education, Junir High School and High School are only two hours in a week, in this little time, seems like it’s enough for a teacher to teach his/her students the contents of each student’s holy kitab especially the based of the character- based curriculum material. This is the basic of the importance of studying holy kitab of every human being, especially students. so a wise teacher must be abble to involve the holy kitab of each student in every material being taught such as Al- Qur’an for Moeslem students’. It is very important for every moeslem teacher to study or interact with the Qur’an as their holy book as the reference for every subject the will tought by them, no exception to science teachers, social teachers and language teachers such as English. Because all references can be found in the Al- Qur;an, specifically for the language mathery Al Qur’an can be used as a media for translating exercises and also as a media for finding examples of words, phrases and examples of sentences. As in teaching noun, verb, adverb and adjective.